Assessment of Human Resource Variables as Correlates of Students’ Performance in Mathematics in Secondary Schools - Osadebe, Patrick U.; Ebikoro, Tebekaemi Omonibo (Advances in Social Sciences Research Journal, 2018)
This study focused on the Assessment of Human Resource Variables as correlates of students’ performance in Mathematics in Secondary Schools in Delta South Senatorial District. The study investigated the relationship between human resource variables and students’ academic performance in Mathematics in Senior Secondary schools. To achieve this purpose, seven research questions and seven hypotheses were raised to guide the study. The theoretical and empirical findings related to the study were reviewed. It was an ex-post facto study with a population of 2,721. A sample of 870 teachers of Senior Secondary Schools were selected through proportionate stratified random sampling techniques from forty Senior Secondary Schools within Delta South Senatorial District. Face and content validity of the instrument used was established. The reliability of the study was determined by the test-retest method and obtained the reliability coefficients 0.72. The scores obtained were analyzed using coefficient of determination and regression method of data analysis. The hypotheses were tested at 0.05 level of significance. Four of the null hypotheses were rejected while three were accepted. The results indicated that staff qualification, teaching experience, specialization of teachers is related to students’ academic performance in mathematics. However, there were no significant relationship between sex, age of teachers and marital status of teachers on students academic performance in Mathematics. From the findings, the study generally recommends that more qualified and professional hands should be encouraged to engage in teaching of mathematics in order to avert the perennial dismal performance of students.